2009
DOI: 10.1042/bsr20090012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of brush border sucrase by polyphenols in mouse intestine

Abstract: The interactions of gallic acid and tannic acid with purified brush border sucrase (EC 3.2.1.48) from mouse intestine have been studied. These findings indicate that both gallic acid and tannic acid inhibit sucrase activity, which is pH dependent. Kinetic analysis revealed that enzyme inhibition by gallic acid is a pure V effect at pH 5.0, which changes to mixed type at pH 7.2, and pure K effect at pH 8.5. In contrast, sucrase inhibition by tannic acid was a pure K effect at acidic pH and uncompetitive type in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…At 2-3 mg/mL, all the extracts (AV, SM, and TO) showed this type of behavior of significant reductions in the two peaks present in the native enzyme, which also suggest significant modifications to PL enzyme structure. The results are consistent with previous studies that have also shown interactions of polyphenols with enzymes can result in conformational changes to the tertiary structure of enzymes (68)(69)(70)(71).…”
Section: Pancreatic Lipasesupporting
confidence: 93%
“…At 2-3 mg/mL, all the extracts (AV, SM, and TO) showed this type of behavior of significant reductions in the two peaks present in the native enzyme, which also suggest significant modifications to PL enzyme structure. The results are consistent with previous studies that have also shown interactions of polyphenols with enzymes can result in conformational changes to the tertiary structure of enzymes (68)(69)(70)(71).…”
Section: Pancreatic Lipasesupporting
confidence: 93%
“…Sucrase inhibitors such as acarbose and voglibose are already used therapeutically in DM patients. In addition, a number of compounds that have inhibitory effects on sucrase have been identified in natural materials, such as green tea [15,16,17]. In contrast, only a few studies have shown inhibitory effects of compounds on invertase [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of maltase was maintained at 10 μL (5 mg/mL), and 15 μL of sample (0.020, 0.030 mg/ml) was measured in various concentrations of maltose (0.025–0.2 mol/L). Km and Vmax were obtained from double-reciprocal line-weaver burk plots [ 16 ]. Acarbose (10 μL, 0.002 mg/mL) and sodium phosphate buffer (15 μL, pH = 6.0) were used as positive and negative controls, respectively.…”
Section: Methodsmentioning
confidence: 99%